Glycemia and farrowing traits in pigs: exploring the association between energetic metabolism and farrowing traits in pigs - Carnevale, Rafaella Fernandes (2022)
Delivering piglets is one of the most demanding activities sows undergo in their lifetime. Sows can have myometrial contractions from two to 12 hours before the first piglet is expelled and also have a nest building behavior. Thus, when the first piglet is delivered the female has already used part of her energy supply. When the sow gets exhausted due to lack of energy, the farrowing process is interrupted, causing great damage to the viability and vitality of the piglets. In this sense, the present study had three main objectives: (1) evaluate how different ingredients modulate the glycemic curve of swine aiming to develop of an energetic supplement to be fed to parturient sows to improve glycemia and farrowing kinetics; (2) evaluate if the peripheral glycemia (measured on ear vein) of sows at the onset of farrowing is related to farrowing traits and, identify risk and protective factors, quantify their effect, and understand how peripheral glycemia interacts with farrowing kinetics; (3) orally fed sows an innovative energetic supplement at onset of farrowing aiming to increase available energy to the uterus, decrease farrowing duration and benefit piglets ’ vitality. Based on the glycemic curves of the studied ingredients, malt extract, resistant starch and glycerol were chosen to compose the energetic supplement. In the second trial, datasets from four farm with sows ’ characteristics and farrowing data were collected. Glycemia was assessed with a portable glucometer, the measurement was performed immediately after the birth of the first piglets, considered as the initial glycemia (IGly) and at the end of farrowing, considered as the final glycemia (FGly). The use of oxytocin, manual assistance and IGly were negatively associated to farrowing duration, whilst total piglets born, and parity were positively associated to farrowing duration. IGly was negatively associated with fasting period (p<0.05). IGly can be used as a tool to identify sows more prone to prolonged farrowing duration The results suggests that the glucose metabolism during farrowing is different and dependent on the glycemia at the onset of farrowing. In the third trial, 180 hybrid commercial sows were blocked according to parity and considered as an experimental unit. Animals were allocated to one of the following treatments: SUP (females supplemented with energetic supplement; n = 95) and CON (non-supplemented females; n = 85). Glycemia was measured at 0. 20. 40, 80 and 180 (T0, T20, T40, T80 and T180, respectively) minutes after farrowing onset. Farrowing kinetics were recorded. Piglets were evaluated for vitality in a score ranging from 0 to 10. Farrowing duration was shorter (p < 0.05) for SUP-sows compared to CON-sows. Glycemia at T0 was similar for both groups (p> 0.05). Sows which received the energy supplement had higher blood glucose (p<0.05) at T20 and T40. At T80 and T180 glycemia did not differ (p> 0.05) between CON-sows and SUP. The 17th and 20th piglets born from CON-sows had decreased values of vitality score (p<0.05) when compared to the same birth order piglets born in the SUP group.